Battle casualties during Iraqi Iranian war 1980-1988 - Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2007)
Background- Every war in the world has its characteristics and the Iraqi Iranian war 1980-1988 has been neglected for along time due to political factors . this study tried to illustrate some of the features of casualties during this war . Methods – review of records of all veterans evacuated to an advanced dressing station (ADS) serving a corps sector over one year starting from the 1st of Jan. 1982 to the 31st of Dec. 1982. Results – the total number of casualties reached this station was 3020 veterans . Mortality rate before reaching to the station was about 20%. The majority of veterans (70%) were evacuated to the next station and most of them (90%) were injured during combat. Severe injuries constituted only 11% of casualties evacuated while the majority of those evacuated were those with intermediate and simple injuries . the most common causative agent was shrapnel in 80% and extremities were the most common injured parts of the body (62%) and abdominal injuries were the least common(3.3%). Conclusion – in spite of all the differences as compared to other war experiences , the mortality, causative factors, severity and site of injuries were comparative to other wars since Vietnam war till the last war in Iraq 2003 with limited differences.